1993
DOI: 10.1111/j.1476-5381.1993.tb13652.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐adrenergic, non‐cholinergic neural activation in guinea‐pig bronchi: powerful and frequency‐dependent stabilizing effect on tone

Abstract: 1 We examined non-adrenergic, non-cholinergic (NANC) stimulation for its stabilizing effect on bronchial smooth-muscle tone with respect to its regulatory power and the effect of variations in neural impulse frequency.2 The guinea-pig isolated main bronchus (n = 4-12) 4 There was a difference of approximately 90% of maximum between the highest and the lowest tone level prior to NANC activation. This difference was reduced by the converging contractile and relaxant NANC responses and the magnitude of this '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…However, it was not until 1988 that the first modern day vagus nerve stimulator was implanted into a patient for intractable epilepsy (30) and 1997 when the FDA approved the Cyberonics Inc.'s VNS Therapy (33). VNS using high voltages, however, is capable of inducing bronchoconstriction in human clinical settings (34) as well as in the animal models (18–24). In contrast, we have shown that the specific low voltage VNS signal applied in this guinea pig histamine model could reduce the Ppi.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, it was not until 1988 that the first modern day vagus nerve stimulator was implanted into a patient for intractable epilepsy (30) and 1997 when the FDA approved the Cyberonics Inc.'s VNS Therapy (33). VNS using high voltages, however, is capable of inducing bronchoconstriction in human clinical settings (34) as well as in the animal models (18–24). In contrast, we have shown that the specific low voltage VNS signal applied in this guinea pig histamine model could reduce the Ppi.…”
Section: Discussionmentioning
confidence: 61%
“…The vagus nerve provides the dominant autonomic innervation of the airways and, through acetylcholine release from its pulmonary nerve endings, triggers bronchoconstriction by direct activation of muscarinic acetylcholine receptors on airway smooth muscle cells (17). Vagus nerve stimulation (VNS) is an important tool for investigating the neural pathways and receptors that control airway smooth muscle tone and when stimulated with relatively high voltages (10–20 V) has been shown to increase bronchoconstriction in a variety of species including guinea pigs (18–20), dogs (21), cats (22), swine (23), and rabbits (24). We have selected the guinea pig animal model for investigating histamine and VNS since it is the more established animal model and has been well validated over the past 25 years for assessments of airway tone (25–28).…”
Section: Introductionmentioning
confidence: 99%
“…However, high concentrations of L‐NOARG failed to alter adult bronchial relaxations to EFS at any of these. In order to compare responses across ages, we precontracted tissues to 50% of the ACh E max , as it has been previously found that the level of muscle tone may influence the size of nerve‐induced inhibitory relaxations and hence the release of NO (Cohen & Berkowitz, 1974; Vargas et al , 1990; Linden et al , 1993).…”
Section: Discussionmentioning
confidence: 99%
“…We could further demonstrate in our study that all nerve-mediated relaxation was blocked by TTX (9). NOreleasing inhibitory nonadrenergic, noncholinergic (iNANC) fibers have repeatedly been shown to be TTX sensitive (10), suggesting that our use of TTX was sufficient to evaluate and discount the possible contribution of NO-mediated neuronal relaxation, the mechanism proposed by Drake and colleagues.…”
mentioning
confidence: 52%